Drawing the pathetic parent creature: Aline Kominsky Crumb in conversation with Sarah Lightman. Issue 2 (1st December 2016) - Lightman, Sarah
In this abridged and edited transcription of '"Arnie's Air Conditioner" and other fond memories: Aline Crumb in conversation with Sarah Lightman', held on 15 April 2016 at The House of Illustration, Kominsky Crumb talks through her role in the history of autobiographical comics, and discusses comics that reflect on her childhood experiences. She also describes how she deliberately approached parenting her daughter, Sophie, differently and how this is reflected in her works.